Ozone and nitrogen dioxide changes in the stratosphere during 1979-84 - Callis, Linwood B.; Natarajan, Murali (1986)
Analyses of stratospheric nitrogen dioxide distributions as measured by four different satellite experiments indicate midlatitude increases of up to 75 percent during the 1979-84 period. These increases are attributed to enhanced upper atmospheric formation of odd nitrogen during solar cycle 21 with downward transport to the stratosphere. The increases in NO2 provide an explanation for the recently observed dramatic springtime minima in the Antarctic ozone and suggest the reason for the reported midlatitude stratospheric ozone decreases observed by satellite and ground-based stations since the mid 1970s.